Comparison of the Detection and Ligation of Patent Processus Vaginalis Between Laparoscopy-Assisted Transscrotal Orchiopexy and Single Scrotal Incision Orchiopexy - Zhao, Weiguang; Su, Cheng; Li, Shoulin; Mo, Zengnan (Frontiers in Surgery, 2022)
This study aimed to compare the detection and ligation of patent processus vaginalis (PPV) between laparoscopy-assisted transscrotal orchidopexy (LATO) and single scrotal incision orchiopexy (SSIO) for low palpable undescended testis (UDT). We performed a retrospective medical record review of transscrotal orchidopexies performed for low palpable UDT at our institution from 2017 to 2019; 33 and 39 boys underwent LATO and SSIO, respectively. Data collection included patient demographics, incidence of PPV, operative time, and clinical outcomes. All 95 testes were delivered into the scrotum. There was no significant difference between the two groups with respect to patients’ age, side, and mean operative time. The incidence of PPV in the LATO group was significantly higher than that in the SSIO group (56.52% vs. 34.69%, P=0.04). The incidence of contralateral PPV in the LATO group was 45%. One patient in the SSIO group underwent unilateral PV ligation and laparoscopic exploration revealed bilateral PPV owing to metachronous contralateral hydrocele. One patient in the LATO group demonstrated obliterated PV in the initial transscrotal procedure, but an ipsilateral PPV was found in the latter laparoscopic procedure. In conclusion, LATO has a higher detection rate and higher ligation of the PPV than SSIO, suggesting that, logically, LATO might help reduce recurrent PPV related issues. However, long-term follow-up results are needed to evaluate the advantages and disadvantages in a larger case series.